2007
DOI: 10.1111/j.1651-2227.2007.00363.x
|View full text |Cite
|
Sign up to set email alerts
|

Short‐term growth in children with eczema during treatment with topical mometasone furoate and tacrolimus

Abstract: Background: Treatment with topical glucocorticoids in children with atopic eczema may be associated with systemic adverse effects, such as suppression of growth.Aim: To asses if treatment with topical mometasone furoate 0.1% or topical tacrolimus 0.1% affects short-term growth in children with atopic eczema. Primary outcome measures were lower leg growth rates measured by knemometry.Methods: Twenty 5-to 12-year-old prepubertal children with atopic eczema were included in a randomised, investigator-blind crosso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(1 citation statement)
references
References 28 publications
0
1
0
Order By: Relevance
“…Various studies have reported that MFO can effectively manage infant eczema (IE). [20][21][22][23][24] However, some infants still experience unsatisfactory outcomes. Fortunately, CL is reported to manage eczema very well.…”
Section: Introductionmentioning
confidence: 99%
“…Various studies have reported that MFO can effectively manage infant eczema (IE). [20][21][22][23][24] However, some infants still experience unsatisfactory outcomes. Fortunately, CL is reported to manage eczema very well.…”
Section: Introductionmentioning
confidence: 99%